2004
DOI: 10.1159/000080817
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary breakpoint analysis on Y chromosomes of higher primates provides insight into human Y evolution

Abstract: Comparative FISH mapping of PAC clones covering almost 3 Mb of the human AZFa region in Yq11.21 to metaphases of human and great apes unravels breakpoints that were involved in species-specific Y chromosome evolution. An astonishing clustering of evolutionary breakpoints was detected in the very proximal region on the long arm of the human Y chromosome in Yq11.21. These breakpoints were involved in deletions, one specific for the human and another for the orang-utan Y chromosome, in a duplicative translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The primary outgroup considered was the cat. The complete list of all BACs used in this Wimmer et al (2005) report can be found in the Excel file of Supplementary Tables. The supplementary file also indicates the BACs used to draw the figures and ancestral karyotypes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outgroup considered was the cat. The complete list of all BACs used in this Wimmer et al (2005) report can be found in the Excel file of Supplementary Tables. The supplementary file also indicates the BACs used to draw the figures and ancestral karyotypes.…”
Section: Methodsmentioning
confidence: 99%
“…The ancestral Y-chromosome was probably considerably smaller in all ancestral karyotypes and has been subject to numerous rearrangements during the evolution of the hominoids (Wimmer et al 2005). More work is needed to determine the evolution of marker order in this chromosome.…”
Section: Sex Chromosomesmentioning
confidence: 99%
“…The non-recombining region of the Y progressively extended to include many more genes, to leave one or two small segment(s) that still recombine(s) with the X, called Pseudo-Autosomal Region(s) (PAR), which ensure(s) a proper segregation of the sex chromosomes (Wilson and Makova, 2009). The abundance of inversions on the Y chromosome suggests that they played a role in recombination suppression (Ross et al, 2005;Wimmer et al, 2005). However, other mechanisms may have also been involved, such as genetic modification of recombination rates.…”
Section: Rise and Fall Of Sex Chromosomesmentioning
confidence: 99%
“…Because therian and avian sex chromosomes arose up to approximately 200 Ma, their Y or W chromosomes retain only a few active genes and consist mainly of repetitive DNA elements, exhibiting only few clues about their autosomal origin or the processes that resulted in their degeneration (Charlesworth B and Charlesworth D 2000). Therefore, it is not certain whether inversions are the cause of recombination suppression or whether inversions occur as a consequence of ceased recombination (Charlesworth et al 2005; Wimmer et al 2005; Wilson and Makova 2009). In the case of the plant Silene latifolia , inversions are not actually associated with the formation of evolutionary strata; the progression of sex chromosome differentiation is gradual rather than a result of large chromosomal rearrangements (Bergero et al 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%